Gambaran Tingkat Pengetahuan Perawat Irna Medikal Dalam Menginterpretasi Hasil Ekg - Rosmalinda - -; Darwin - Karim; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this study was to identity description in medical ward to interprete the result of electrocardiogram. The metode of thus study was describtion that conducted in medical ward Arifin Achmad Hospital Pekanbaru. The total of respondent was 69 in 6 ward (Nuri I, Nuri II, Murai I, Murai II, Merak II, Melati). The method was quota sampling. The data was idected by questionnare. The research  used  univariate analysis. Based on the results of research conducted, the data obtained a good knowledge as 28 respondents (40, 6%), quite as 20 respondents (29%), approximately as 21 respondents (30.4%). The results of this study recommend the hospital to hold a training electrocardiogram in the room, so the nurse will be able to handle and identify patients with emergency conditions frequently encountered in everyday practice. Keywords: interpretation electrocardiogram, knowledge, ward Reference: 45 (2001-2012)